The states of mental health of university students majored in mining and interventions based on courses - Liu Haijuan; He Ziming; Chen Panpan (矿业科学学报, 2023)
The SCL-90 was applied to the students from China University of Mining and Technology Beijing with entry year between 2016 to 2019 to exam their mental health status, and the survey result had been compared and analyzed with the Chinese undergraduate norm.Results: from the overall mental health perspective, students majoring in mining showed a certain kind of mental health problems, but no significant differences comparing with the national undergraduates status; As for the types of mental health problem encountered, the students majoring in mining were observed with issues such as obsessive symptoms, sensitive interpersonal relationship, paranoid, depression and psychotic symptoms etc.Based on the above mentioned mental health problems, we have developed on strengthening the construction of courses, improving the students mental health status through multiple approaches.